A review of current trends and future directions in the medical ethnobotany of Gilgit-Baltistan (Northern Pakistan) - Abbas, Zaheer; Bussmann, Rainer W; Khan, Shujaul Mulk; Arshad Mehmood Abbasi (Ethnobotany Research and Applications, 2022)
Background: Ethnobotanical studies play an important role in understanding the plant diversity, bio-cultural variability, utilization of plant-based resources, drug discovery and conservation efforts. The current paper reviews and assesses the ethnobotanical literature and documented medicinal plants of the region of Gilgit-Baltistan, Northern Pakistan. Methods: Relevant literature was searched using electronic scholarly databases Google Scholar, Google, Scopus, Sciences Direct, PubMed, Medline and Web of Science internet websites were extensively browsed using different 24 terms as key words. A total of twenty-four (24) academic journal articles published from 2002 – 2020 were reviewed. Results: Geographically, 54% articles were from Karakorum Range, 75% form Gilgit sub region and 25% Gilgit district. Ethnic-wise 58% of the studies were conducted on Shinas, 25% on Baltis and 12.5% on Brushiski while Wakhi and Khwar were least explored. For data collection interview methods were solely used. A total of 413 plant species were used for 3160 remedies in 224 genera and 79 families from both wild (83%) and cultivated sources (16%). Asteraceae, Rosaceae and Fabaceae were the most used plant families with 58, 36 and 32 species respectively. Artemisia was the leading genus with 11 species followed by Prunus (9 species). Salix, Saussurea, Potentilla, Astragalus and Allium contributed seven (7) species each. Regarding habit herbaceous species were most commonly used (310 species, 75%) and shrubs and trees showed comparatively less contribution with 53 (12%) and 49 (11%) species. Article quotation of the recorded species indicated that, Hippophae rhamnoides and Thymus linearis were the most important medicinal species with highest AQ values (number of reports)17 i.e. reported by 70% of the articles. These recorded species were used to treat 353 disease types for different human body systems. Conclusion: The region of GB is still poorly investigated ethnobotanically, and limited literature found on this subject. However, the diverse medicinal flora of Gilgit-Baltistan validated the regional potential of phytomedicines despite scarce research efforts. GB territory possesses three national parks and current study may be fruitful to develop strategies for regional biodiversity conservation and natural resource management. Keywords: Indigenous knowledge, medicinal plants, mountain ecosystem, natural resources